2013
DOI: 10.1142/s0219843613500151
|View full text |Cite
|
Sign up to set email alerts
|

How Deeply Do We Include Robotic Agents in the Self?

Abstract: In human-human interactions a consciously perceived high degree of self-other overlap is associated with a higher degree of integration of the other person's actions into one's own cognitive representations. Here, we report data suggesting that this pattern does not hold for human-robot interactions. Participants performed a social Simon Task with a robot, and afterwards indicated the degree of self-other overlap with the help of the Inclusion of the Other in the Self (IOS) scale. We found no overall correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the joint Simon task, we replicated the joint Simon effect with a robotic co-actor, concurrent with previous studies (Stenzel et al, 2012; Stenzel et al, 2013; Wen and Hsieh, 2015; Bunlon et al, 2018). Contrary to expectations, the size of the joint Simon effect was not affected by our manipulation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the joint Simon task, we replicated the joint Simon effect with a robotic co-actor, concurrent with previous studies (Stenzel et al, 2012; Stenzel et al, 2013; Wen and Hsieh, 2015; Bunlon et al, 2018). Contrary to expectations, the size of the joint Simon effect was not affected by our manipulation.…”
Section: Discussionmentioning
confidence: 64%
“…The congruency effect in this paradigm is called the ‘joint Simon effect.’ Importantly for our purposes, the joint Simon effect was also obtained in a study where a human participant worked side-by-side with a robot (Stenzel et al, 2012), and the effect was larger when participants were either told that the robot was programmed in a “biologically inspired, autonomous way” than when they were told that it was programmed in a “purely deterministic way.” Another recent study found a joint Simon effect in virtual reality both when the co-actor was a human hand and when it was a robotic hand (Bunlon et al, 2018). Stenzel et al (2013) similarly found a joint Simon effect for a robotic co-actor, but failed to find a relationship between the size of the effect and explicit self-other inclusion, as measured by asking participants which of six images ranging from widely separated to highly overlapping circles best described the relation between the participant and the robot (the Inclusion of the Other in the Self scale, IOS). The latter is striking from the point of view of the feature overlap hypothesis, though it might be accounted for by the fact that there was no manipulation of self-other similarity.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, Sebanz et al ( 2003 ) concluded that other’s action is regarded as similar to ones own action and other’s task is regarded as own task, making the JSE a measure of the co-representation of other person’s action (Sebanz, et al, 2005 ). Based on studies showing that JSE-like compatibility effects are also established when one of the two human co-actors is replaced by an event-producing object (Dolk, et al, 2013 ; Puffe, Dittrich, & Klauer, 2017 ; Stenzel & Liepelt, 2016 ), for instance a puppet (Müller, et al, 2011 ) or a humanoid robot (Stenzel et al, 2012 ; Stenzel, Chinellato, del Pobil, Lappe, & Liepelt, 2013 ), a sole mechanism of action co-representation accounting for the JSE and JSE-like effects has been questioned (Dolk, et al, 2011 , 2014 ; Klempova & Liepelt, 2016 ). Based on the theory of event coding (Hommel, Müsseler, Aschersleben, & Prinz, 2001 ), the referential coding account has been proposed for joint action (Dolk, et al, 2014 , 2013 ).…”
Section: The Joint Simon Effect As a Measure Of Bodily Self-other Integrationmentioning
confidence: 99%
“…The social Simon effect varies in strength, partly due to the relatively small samples (usually around 20, with the highest N being 48 to our knowledge; Stenzel et al 2013 ) that have been used in earlier work (Dolk et al 2011 ; Ruys and Aarts 2010 ; Sebanz et al 2003 ; Vlainic et al 2010 ). Another reason for the variation in the strength of the social Simon effect pertains to the observation that the effect depends on contextual as well as individual differences (Aron et al 1992 ; Colzato et al 2012a , b , 2013 ; Decety and Sommerville 2003 ; Humphreys and Bedford 2011 ; Müller et al 2011 ; Slotter and Gardner 2009 ).…”
Section: Introductionmentioning
confidence: 94%